Answer:
The answer is "A point on the parabola and Focus".
Explanation:
![= √((x - x)^2 + (y- (-p))^2) = √((x-0)^2+ (y-p)^2) \\\\= √((0)^2 + (y+p))^2) = √((x)^2+ (y-p)^2) \\\\= √((y+p))^2) = √((x)^2+ (y-p)^2) \\\\= (y+p) = (x)+ (y-p) \\\\= y+p = x+ y-p \\\\=2p=x\\\\=x=2p](https://img.qammunity.org/2022/formulas/mathematics/high-school/1tdxqm30x832x88gbtfvu8wp68hoovhu3i.png)
Whenever the focus and also the guideline are utilized in determining the parabolic formula, two distances have indeed been equal.
The distance from the direction, as well as a parabolic point, was equal to the distance from the center to a parabolic point.